2019
DOI: 10.1186/s12912-019-0361-z
|View full text |Cite
|
Sign up to set email alerts
|

Patients’ perception of quality of nursing care; a tertiary center experience from Ethiopia

Abstract: Background Nursing care closely influences patients’ satisfaction with the overall quality of care, and the importance of measuring patient satisfaction with nursing care cannot be emphasized enough. Data are however scarce regarding patients’ perception of quality of nursing care in Ethiopia. We performed this study to assess patient’s perception of the quality of nursing care in a tertiary center in Ethiopia. Methods Data were collected prospectively using Quality of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
39
1
5

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(60 citation statements)
references
References 32 publications
4
39
1
5
Order By: Relevance
“…Although this is the first study to extensively examine the literature on this topic, our finding suggests there is limited evidence. Pregnant women’s perception of the quality of care is a key performance metric of health services hence, it is worth studying since it can influence service utilization [ 59 , 60 ]. Additionally, as healthcare stakeholders continue to search for initiatives that improve positive pregnancy experiences and outcomes, this study’s results have demonstrated the need for more researches to inform policy decisions and improve maternal healthcare [ 61 ].…”
Section: Discussionmentioning
confidence: 99%
“…Although this is the first study to extensively examine the literature on this topic, our finding suggests there is limited evidence. Pregnant women’s perception of the quality of care is a key performance metric of health services hence, it is worth studying since it can influence service utilization [ 59 , 60 ]. Additionally, as healthcare stakeholders continue to search for initiatives that improve positive pregnancy experiences and outcomes, this study’s results have demonstrated the need for more researches to inform policy decisions and improve maternal healthcare [ 61 ].…”
Section: Discussionmentioning
confidence: 99%
“…Not surprisingly, the results of most studies conducted in Iran and other countries have further established a negative gap in the quality of services provided by hospitals [ 14 , 32 34 ]. The fact is that customers of medical centers are not physically and mentally well, once they are admitted.…”
Section: Discussionmentioning
confidence: 99%
“…In a way, this is to distance the health team, not bring it nearer to the people. As some researchers are coming to conclude, time and resources spent on training staff and conducting interviews and focus group discussions may well be better directed towards training staff in engaging directly with communities in the consideration of their needs and priorities (Gishu et al, 2019).…”
Section: What Kinds Of Strengthening Are Essential To the Developmentmentioning
confidence: 99%